Israel's restoration : a textual-comparative exploration of Ezekiel 36-39 - Crane, Ashley S. (Brill, 2008)
Commentators traditionally use a textual-critical methodology in examining Hebrew and Greek manuscripts to establish an 'original' reading, frequently attributing other variants to scribal error. This book proposes a complementary-textual comparative methodology that treats each Hebrew and/or Greek manuscript with equal value.
Keywords: Bible. -- Ezekiel, XXXVI-XXXIX -- Criticism, Textual.; Bible. -- Ezekiel, XXXVI-XXXIX. -- Greek -- Versions.; Bible. -- Ezekiel, XXXVI-XXXIX -- Comparative studies.; Bible. -- Ezekiel, XXXVI-XXXIX -- Criticism, interpretation, etc., Jewish.; Bible. -- Old Testament. -- Greek -- Versions -- Septuagint.; Bible. -- Old Testament; Bibel -- Ezechiel -- 36-39; Bibel -- Altes Testament -- Masoretischer Text; Bibel -- Altes Testament -- Septuaginta; RELIGION -- Biblical Studies -- Prophets.; Textkritik; Textvergleich; Comparative studies; Criticism, interpretation, etc.